Efficient implementation of a numerical model for flexible net structures. (15th February 2018) - Martin, T.; Schacht, S.; Riesen, P.; Paschen, M.
Abstract: A numerical model for the determination of the deformed shape of nets fixed in a stiff frame is presented. The tension element method is able to predict the steady-state solution of a net in a prescribed flow under consideration of hydrodynamic loads and elastic twines. It is based on a discretisation of the net in mass points connected with straight bars. The successive approximation is applied to the system which leads to a significant reduction of the resulting system size in comparison to the matrix of a Newton-Raphson method. This is caused by the ability to solve the system for unit bar vectors and not for knots. Thus, the inverse can be calculated faster and more stable. So far, the advantage of high accuracy and physical comprehensibility by taking geometrical constraints into account is balanced by the difficulties in defining the essential directions of unit vectors properly. The new implementation provides this information using an efficient technique which is adapted from finite volume methods. Measurements are provided in order to validated the method at the end of this paper. A comparison shows the principal working of the code as well as the high accuracy of the method for steady-state problems. Highlights: A numerical method for calculating the deformations of nets is presented. Remarks regarding an efficient implementation for practical purposes is provided. The model capabilities are validated with experimental data.